GATT Translation Method for Elementary Mandarin Learners / Hoe Foo Terng - Terng, Hoe Foo (Universiti Teknologi MARA, Kedah, 2014)
With China's economy blooming, many will take up Mandarin as it gains more popularity. In Malaysia, the number of non-Chinese learners taking up Mandarin as a foreign language is considerable. Apart from primary schools offering Mandarin classes, all of the public universities have also offered Mandarin courses for their students in order for them to improve their chances of employment. As learning Mandarin has become a trend, one cannot simply teach the subject and hope that learners can pick up the language. As there are diverse choices of learning methods, learners nowadays also hope to systematically learn and see their learning progress within a shorter time. Like most of the language learners, they will be very active in the beginning. When they do not achieve the desired result, their enthusiasm subsides, and they soon begin to lose interest. If the learner can grasp the accurate method of constructing grammatically correct simple sentences in a short time, they will have confidence to continue their learning. When the learner cannot find a proper way to learn, they will fall back on their first language learning experience. This negative transfer will affect the foreign language learning and more often than not, result in the construction of many incorrect and awkward sentences. GATT (Grouping- Arranging-Translating-Touch up) translation method which is derived from WSD (Words Sequence Diagram), is a method which helps learners to place the words in a correct sequence to form grammatically correct sentences. It can minimize the negative transfer of the mother tongue. Lastly, GATT translation method will guide learners through a step by step approach to complete the task of sentence construction and free learners from the fear of not knowing how to proceed.